Institutional Arrangements for Conservation, Development and Tourism in Eastern and Southern Africa A Dynamic Perspective - Duim, René van der (Springer, 2015)
This book is about institutional arrangements at the intersection of conservation, development and tourism. More specifically, it discusses and compares distinctive arrangements in eastern and southern Africa, ranging from conservancies in Namibia, community-based organizations in Botswana, tourism-conservation enterprises in Kenya, private game reserves in South Africa and sport hunting in Uganda, to transfrontier conservation areas...